2014
DOI: 10.1111/ger.12175
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the efficiency of humic acid to remove micro‐organisms from denture base material

Abstract: Humic acid could be used as an alternative 'natural' solution for denture-cleaning agent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…C. albicans , S . aureus , E. faecalis (gram‐positive) and P. aeruginosa (gram‐negative) are some of the microorganisms evaluated from the microbiota of old complete dentures and that were also found in implant‐supported fixed complete dentures from our study 30,31 …”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…C. albicans , S . aureus , E. faecalis (gram‐positive) and P. aeruginosa (gram‐negative) are some of the microorganisms evaluated from the microbiota of old complete dentures and that were also found in implant‐supported fixed complete dentures from our study 30,31 …”
Section: Discussionmentioning
confidence: 59%
“…30 C. albicans, S. aureus, E. faecalis (gram-positive) and P. aeruginosa (gram-negative) are some of the microorganisms evaluated from the microbiota of old complete dentures and that were also found in implant-supported fixed complete dentures from our study. 30,31 The observed Candida genera did not vary among the evaluated patients: Candida albicans was the most verified species checkerboard method. In some studies, C. albicans was the main species isolated in complete denture wearers, 27,32 followed by Candida tropicalis.…”
Section: Discussionmentioning
confidence: 85%
“…The previous study [14] showed that humic acid solution significantly reduced the microorganisms on dentures. However, beside the effectiveness of the introduced experimental solution, the side effects of the solution, such as discoloration or surface deterioration of dentures, were not evaluated in the study.…”
Section: Discussionmentioning
confidence: 94%
“…Humic acid has recently been introduced as an alternative denture-cleaning agent. The effect of humic acid to remove microorganisms from denture base material was reported [14] . Humus is that organic portion of soil that remains after millions of years of microbial decomposition of plants and vegetation.…”
Section: Evaluating the Efficiency Of Humic Acid To Remove Stain Frommentioning
confidence: 99%